PENERAPAN KOMUNIKASI PARTISIPATIF PADA PEMBANGUNAN DI INDONESIA - Karmila Muchtar (Fakultas Komunikasi, Sastra, dan Bahasa, 2016)
Participative Communication is an innovation system directed mainly applying bottom-up and participative communication approach of the society. Participative communication provide space for people to exchange information and knowledge . Application of the principle of participative communication is done through dialogue. The study aims to get descriptions on how participative communication can be applied on the various program in Indonesia. The study has been done using survey about variables descriptive analysis. In general, the concept of participative communication is a fresh concepts for development in Indonesia, but the implementation has not been work in accordance with the concept, with the result that the main purpose of development not successful. To increase partisipative communication process, facilitators should carry out more intensive approach and to involve those society who considered as leaders of the society group, i.e to active. Partisipative communication should be maintained through the various program in such that development can be maintained and increased